Desempenho produtivo, avaliação da cecotrofia, digestibilidade in vitro e in vivo de coelhos em crescimento alimentados com bagaço de cana-de-açúcar in natura ou autoclavado e vinhaça - Felipe Norberto Alves Ferreira (2018)
The current study was conducted to evaluate the potential use of in natura or autoclaved sugarcane bagasse, enriched or non-enriched with vinasse, in diets for growing rabbits, by assessing the growth and slaughtering performance, in vitro digestibility, degradability and fermentation parameters. A total of 110 rabbits were used, distributed in five groups with 22 animals each in a completely randomized design and fed diets containing: 100 g/kg of in natura sugarcane bagasse (INB); 100 g/kg of in natura sugarcane bagasse enriched with vinasse (INBV); 100 g/kg of autoclaved sugarcane bagasse (AB); 100 g/kg of autoclaved sugarcane bagasse enriched with vinasse (ABV); and a control diet, without bagasse or vinasse. The in vitro assays were conducted employing cecum inoculum on the same aforementioned dietary treatments. The results showed that all bagasses show high amounts of aNDF (742 to 900 g/kg DM), ADF (493 to 616 g/kg DM) and lignins (88.1 to 136 g/kg DM), and low CP (22.6 to 30.3 g/kg DM). The inclusion of vinasse increased the in vitro DM digestibility and in vitro DM degradability of the diets (0.72 and 0.67, respectively). The control diet presented higher in vitro DM degradability (0.68) when compared to INB (0.65) and AB (0.65), but was no significantly different to the INBV (0.67) and ABV (0.66) diets. For diets with autoclaved bagasse, vinasse inclusion increased the specific gas production rate from 4.33 to 4.74. Maximum fermentation rate was higher for ABV than for INBV diet (6.09 vs. 5.54 mL/h, respectively), and the autoclaving of bagasse and inclusion of vinasse increased the lag time. Bagasse autoclaving increased FCR from 30 to 51 days (2.26 vs. 2.44), and FCR from 51 to 72 days was reduced by inclusion of vinasse (4.84 and 5.28). There were no significant differences to live weight, ADG, ADFI and slaughter weight among the groups. Autoclaving bagasse reduced the relative liver weight and increased caecal N-NH3 content. Moreover, the N-NH3 of the control group (3.71 mmol/L) was lower than INBV (4.64 mmol/L), AB (5.01 mmol/L) and ABV (5.11 mmol/L), but similar to the INB group (4.05 mmol/L). The results of this study revealed that 100 g/kg of sugarcane bagasse can be included in the diet of growing rabbits without adverse effects on growth performance. Additionally, autoclaving and vinasse inclusion promote higher rate and extent of in vitro digestion, which is reflected on the caecal activity.